Pengendalian Persediaan Dies Mesin FM Menggunakan FSN Analysis Berdasarkan Turn Over Ratio pada Departemen Produksi - Zahra, Shakila Divala; Winarno, Winarno; Alfanadim, Andraya (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Effective inventory management is essential for manufacturing companies to ensure smooth production processes. This study was conducted in the Production Department, which faces challenges in managing the inventory of FM Machine dies, including irregular stock turnover, an excess of rarely used items, and shortages of high-rotation items. This research aims to apply the Fast Moving, Slow Moving, Non-Moving (FSN) Analysis method based on the Turn Over Ratio (TOR) to classify inventory according to its movement levels. Historical inventory data of dies from January to December 2023 were analyzed to calculate average inventory, partial TOR, storage duration, and annual TOR. The results showed that out of 53 types of dies, 43% were categorized as Fast Moving, 32% as Slow Moving, and 25% as Non-Moving. These findings provide a framework for optimizing inventory management by prioritizing procurement based on actual needs. In conclusion, the FSN Analysis method based on TOR is effective in creating an efficient inventory management system, reducing storage costs, and ensuring the availability of items to support smooth operations. This study contributes by presenting a practical approach that can be applied across various manufacturing sectors to enhance production efficiency. Keywords: FSN Analysis, Inventory Management, Manufacturing, Production, Turn Over Ratio